The case series of baclofen intoxication - Kos, Michał; Drankowska, Justyna; Kościuk, Andrzej; Widłak, Karolina; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Baclofen, a gamma-amino butyric acid type B (GABAb) inhibitor, is commonly used in management of spasticity and other medical conditions, such as alcohol dependency. However, given its mechanism of action, increasing usage of baclofen raises concerns about possibility of intoxication. The authors present herein three cases of baclofen intoxication of patients in various age and general condition.